Development of supply chain performance management tool - Bhargava Prateek (2015)
A supply chain is a system of organizations, people, activities, information, and resources involved in moving a product or service from supplier to customer. Supply chain activities transform natural resources, raw materials, and components into a finished product that is delivered to the end customer. Supply Chain Management (SCM) is the management of the flow of goods and services. It includes the movement and storage of raw materials, work-in-process inventory and finished goods from point of origin to point of consumption. Supply chain management is a crucial process for many companies, and many companies strive to have the most optimized supply chain because it usually translates to lower costs for the company. For effective supply chain management, KPIs and metrics are used to track the performance of the supply chain over a given period of time. A key performance indicator (KPI) is a measurement or a metric used to evaluate the performance of a unit or a process that plays an important part in the success of an organization. KPIs are of utmost importance to the organizations to present information on the performance of various levels of the organization. The key to success is selecting KPIs that will add value in the long-term to the organization. Apart from the selection, the visualization of the KPI is as important to convey the correct information to the manager through data representation in a simple yet effective manner. This report will document the development of a supply chain management tool developed as a dashboard application with the software MS Excel. This supply chain management tool is developed using Excel Macros and Visual Basic Application (VBA). It enables the managers of SMEs to manage their supply chain in a faster and effective way by tracking and analysing KPIs essential to their organisation. The tool makes use of various data visualization methods such graphs, gauges and scorecards to enable the users analyse the data efficiently at a glance and provide a screenshot of their company’s supply chain performance. The tool also provides an in-depth analysis of each KPI to help the managers find out the root cause of a sub-par performance of a particular KPI and pinpoint the location of the problem.